2019
DOI: 10.25105/urbanenvirotech.v0i0.4361
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Water Quality Status in the Ngebrong River With Physical and Chemical Parameters in the Tawangsari Barat Region, Pujon District, Malang Regency

Abstract: <strong>Aim:</strong> The purpose of this study was to determine the status of water quality in a river by using the Pollution Index method as stated in the Decree of the Minister of Environment No. 115/2003 regarding Guidelines for Determining the Status of Water Quality and to determine the effect of quality status on development efforts towards ecotourism. <strong>Methodology and Results:</strong> The measurement of water quality was carried out at two points, namely T1 (upstream) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The COD parameter at February in all sampling location were exceeded the quality standard while at April in the locations of Telukjambe and East Adiarsa were still below the quality standard. Higher COD concentration shows that the organic content cannot be degraded biologically (Suharto et al, 2019) The BOD parameters in all sampling locations at February and April showed exceeding quality standards. (Ling et al, 2012).…”
Section: Resultsmentioning
confidence: 89%
“…The COD parameter at February in all sampling location were exceeded the quality standard while at April in the locations of Telukjambe and East Adiarsa were still below the quality standard. Higher COD concentration shows that the organic content cannot be degraded biologically (Suharto et al, 2019) The BOD parameters in all sampling locations at February and April showed exceeding quality standards. (Ling et al, 2012).…”
Section: Resultsmentioning
confidence: 89%
“…Part of this domestic waste is generated from household activities, in the form of solid waste (rubbish) from food scraps, packaging, yard waste, and waste water from water used for bathing, washing, cooking and other activities. This household waste enters the sewerage and eventually enters the river flow and becomes a burden of river pollution (Mantaya et al, 2016;Suharto et al, 2019).…”
Section: Calculation Of Potential Domestic Pollutant Loadmentioning
confidence: 99%
“…Peningkatan aktivitas masyarakat cenderung menimbulkan pencemaran dan mengganggu kelestarian suatu perairan (Suharto, 2019). Limbah domestik berasal dari permukiman masyarakat sekitar yang melakukan berbagai kegiatan, seperti mandi, mencuci, buang air kecil dan membuang sampah pada bantaran Situ Gede.…”
Section: Pendahuluanunclassified